2015
DOI: 10.1093/femsyr/fov010
|View full text |Cite
|
Sign up to set email alerts
|

A series of conditional shuttle vectors for targeted genomic integration in budding yeast

Abstract: The capacity of Saccharomyces cerevisiae to repair exposed DNA ends by homologous recombination has long been used by experimentalists to assemble plasmids from DNA fragments in vivo. While this approach works well for engineering extrachromosomal vectors, it is not well suited to the generation, recovery and reuse of integrative vectors. Here, we describe the creation of a series of conditional centromeric shuttle vectors, termed pXR vectors, that can be used for both plasmid assembly in vivo and targeted gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…After transformation into yeast, we identified a strain bearing a single integrant of the YIp construct and confirmed that strains bearing a YCp produced relatively similar fluorescence levels (data not shown). As previously observed (Chou et al, ; Gnügge et al, ; Jensen et al, ), strains bearing YIp or YCp constructs produce dissimilar histograms of GFP expression when assayed by flow cytometry (Figure a). Even in plasmid‐selecting medium, a proportion of cells transformed with a YCp (blue histogram) appear to lose the plasmid and are optically dark (peak to the far left).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…After transformation into yeast, we identified a strain bearing a single integrant of the YIp construct and confirmed that strains bearing a YCp produced relatively similar fluorescence levels (data not shown). As previously observed (Chou et al, ; Gnügge et al, ; Jensen et al, ), strains bearing YIp or YCp constructs produce dissimilar histograms of GFP expression when assayed by flow cytometry (Figure a). Even in plasmid‐selecting medium, a proportion of cells transformed with a YCp (blue histogram) appear to lose the plasmid and are optically dark (peak to the far left).…”
Section: Resultssupporting
confidence: 83%
“…Those plasmids, in turn, have been transformed into thousands of yeast strains, including strains bearing empty pRS40x vectors for use as controls. Potential users of the ICE plasmids series should be aware, though, that a tremendous amount of effort has been put into updating and redesigning yeast shuttle vectors (Chee & Haase, ; Chou et al, ; Fang et al, ; Frazer & O'Keefe, ; Gnügge et al, ; Jensen et al, ; Lian et al, ). These include both updates to the pRS40x series, such as the removal of restriction sites from yeast selectable markers to increase the number of unique cutters in the multiple cloning site (MCS; Chee & Haase, ), as well as completely redesigned vector backbones (Gnügge et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[44] Furthermore, yeast homologous recombination has recently been used to assemble conditional shuttle vectors for yeast chromosomal integration. [50] The autonomous replication sequence and centromere of the constructed shuttle vectors are flanked by loxP sites targeted by Cre site-specific recombinase. In the extrachromosomal form, shuttle vectors can be used as backbones for yeast homologous recombination-mediated DNA assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of Cre recombinase initiates excision of the autonomous replication sequence and centromere-harboring cassette which leads to integration of the vector into the chromosome at a targeted locus. [50] In vivo DNA assembly in B. subtilis…”
Section: Introductionmentioning
confidence: 99%